A novel UWB flexible antenna with dual notch bands for wearable biomedical devices - Dilruba Geyikoglu, Miraç (Analog integrated circuits and signal processing, 2023)
This study presents a novel UWB flexible antenna with dual band-notched design for wearable biomedical devices. The proposed antenna is designed on Kapton Polyimide-based flexible substrate. This includes a CPW fed circular and triangle structure. The dual notched bands are realized by using two triangular-shaped spiral slots defected ground structures. The first notched band (2.4–3.7 GHz) is generated for rejecting WLAN and WiMAX, the second notch (5.15–5.725 GHz) is generated for rejecting HyperLAN/2. The designed UWB antenna has approximately a bandwith of 159% (2.05–14 GHz) in simulation. Thus, the designed UWB antenna meets FCC standards. The antenna has an omnidirectional radiation pattern with a maximum gain of 12.7 dB in 8.4 GHz. The proposed antenna is fabricated with the low-cost airbrush printed technique. In this technique, a higher gain value is obtained by controlling the thickness of the conductive layer. Effect of flexibility on the antenna performance is tested for different configurations in the simulation and anechoic chamber environments. According to the results obtained, the overall performance is not affected except for the shift in frequency. Since the antenna has a UWB structure, the frequency shift that occurs in bending is at a tolerable level. The proposed UWB antenna is suitable for wearable biomedical devices, with a high UWB performance.